Analysis of Voice Signal Phase Data Informativity of Authentication System User - Pastushenko, M.; Krasnozheniuk, Y.; Lemeshko, O. (ХНУРЕ, 2020)
Directions of improving the quality characteristics specific to voice authentication systems in various access systems are analyzed and explored in the article. One of the main directions for improving the quality characteristics of the user authentication systems is the use of phase information of a voice signal. The urgent scientific task of studying new procedures is being solved to refine the estimates of the pitch frequency obtained on the basis of the amplitude-frequency spectrum analysis. The estimates were refined using phase data of the voice signal, as well as estimates of the pitch frequency in the process of obtaining cepstral coefficients. The results are obtained in the course of statistical analyzing the simulation results using experimental voice data of the authentication system user. Phase data of a voice signal allows obtaining adequate and reliable estimates in the process of spectral analysis. However, if there are errors associated with gross errors, for example, when taking the first or second formants for estimating the pitch frequency, preference should be given to the estimate obtained in the process of calculating cepstral coefficients. The presented research results should be used in voice authentication systems, improving speech recognition systems, as well as in solving speaker identification problems.
Keywords: amplitude; authentication; voice signal; information; spectrum; phase; pitch frequency